Smartphone Addiction and Interpersonal Competence of Nursing Students - Sunhee LEE; Hye-Jin KIM; Han-Gyo CHOI; Yang Sook YOO (Tehran University of Medical Sciences, 2018)
Background: Interpersonal competence is an important capacity for nurses. Recently, the advent of smartphones has instigated considerable changes in daily life. Because smartphone has multiple functions, people tend to use them for numerous activities, often leading to addictive behavior. Methods: This cross-sectional study performed a detailed analysis of smartphone addiction subscales and social support related to interpersonal competence of nursing students. Overall, 324 college students were recruited at Catholic University in Seoul, Korea from Feb 2013 to Mar 2013. Participants completed a self-reported questionnaire, which included scales that measured smartphone addiction, social support, interpersonal competence, and general characteristics. Path analysis was used to evaluate structural relations between subscales of smartphone addictions, social support, and interpersonal competence. Results: The effect of cyberspace-oriented relationships and social support on interpersonal competence were 1.360 (P=.004) and 0.555 (P<.001), respectively. Conclusion: Cyberspace-oriented relationship, which is a smartphone addiction subscale, and social support were positively correlated with interpersonal competence of nursing students, while other smartphone addiction subscales were not related to nursing student interpersonal competence. Therefore, effective smartphone teaching methods be developed to enhance nursing student motivation